Второе призвание: [очерки] / О. Д. Балдина - Балдина Ольга Дмитриевна (Молодая гвардия, 1983)
Экземпляры: КХ (20120531) / Инвентарный номер: 808443 / Цена: 0.95 / Сис.шифр: 73/76 / Авт.знак: Б 20 / ГРНТИ: 18 / ББК: 85.7